2020
DOI: 10.1080/15384101.2020.1747776
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA MCF2L-AS1 controls osteogenic differentiation by regulating miR-33a

Abstract: Bone homeostasis is maintained by balanced osteoblast-mediated tissue production and osteoclastmediated tissue destruction, and is disrupted in pathological conditions such as osteoporosis. The mechanisms underlying osteogenic differentiation of bone marrow mesenchymal stem cells, which is critical to bone homeostasis, are not completely clear, despite extensively studies. Long noncoding RNAs (lncRNAs) have recently emerged as novel therapeutic targets in various diseases. However, the expression pattern and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Although the role of RP11-84C13.1 in osteoporosis has been preliminarily studied, our current knowledge of its basic pathophysiological mechanism remains unclear. To date, multiple RNA transcripts, such as lncRNAs and circular RNAs, have been revealed to function as competitive endogenous RNAs by miRNA binding ( 26 , 27 ). Wang et al ( 28 ) revealed that lncRNA KCNQ1OT1 promoted BMP2 expression to regulate osteogenic differentiation by sponging miRNA-214.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of RP11-84C13.1 in osteoporosis has been preliminarily studied, our current knowledge of its basic pathophysiological mechanism remains unclear. To date, multiple RNA transcripts, such as lncRNAs and circular RNAs, have been revealed to function as competitive endogenous RNAs by miRNA binding ( 26 , 27 ). Wang et al ( 28 ) revealed that lncRNA KCNQ1OT1 promoted BMP2 expression to regulate osteogenic differentiation by sponging miRNA-214.…”
Section: Discussionmentioning
confidence: 99%
“…This could lead to inhibition of osteoblast differentiation. Thus, MCF2L-AS1 stimulated osteogenic differentiation in BMSCs by positively regulating the expression of Runx2 (Chen et al, 2020).…”
Section: Lncrna Involved In Bmsc Regulation Through Mirnamentioning
confidence: 90%
“…Chen et al [56] studied the role of lncRNA MCF2L-AS1 in BMSC osteogenic differentiation and the underlying molecular mechanisms. Microarray analysis was performed to detect lnRNA expression during the hBMSC osteoinduction, identifying nine upregulated lncRNAs and fifteen downregulated lncRNAs, according to the absolute fold change ≥ 1.5 and p-value ≤ 0.05.…”
Section: Lncrnas As Positive Regulatorsmentioning
confidence: 99%